In situ preparation of Fe3O4 in a carbon hybrid of graphene nanoscrolls and carbon nanotubes as high performance anode material for lithium-ion batteries. (23rd October 2017) - Liu, Yuewen; Hassan Siddique, Ahmad; Huang, Heran; Fang, Qile; Deng, Wei; Zhou, Xufeng; Lu, Huanming; Liu, Zhaoping
Abstract: A new conductive carbon hybrid combining both reduced graphene nanoscrolls and carbon nanotubes (rGNSs-CNTs) is prepared, and used to host Fe3 O4 nanoparticles through an in situ synthesis method. As an anode material for LIBs, the obtained Fe3 O4 @rGNSs-CNTs shows good electrochemical performance. At a current density of 0.1 A g −1, the anode material shows a high reversible capacity of 1232.9 mAh g −1 after 100 cycles. Even at a current density of 1 A g −1, it still achieves a high reversible capacity of 812.3 mAh g −1 after 200 cycles. Comparing with bare Fe3 O4 and Fe3 O4 /rGO composite anode materials without nanoscroll structure, Fe3 O4 @rGNSs-CNTs shows much better rate capability with a reversible capacity of 605.0 and 500.0 mAh g −1 at 3 and 5 A g −1, respectively. The excellent electrochemical performance of the Fe3 O4 @rGNSs-CNTs anode material can be ascribed to the hybrid structure of rGNSs-CNTs, and their strong interaction with Fe3 O4 nanoparticles, which on one hand provides more pathways for lithium ions and electrons, on the other hand effectively relieves the volume change of Fe3 O4 during the charge–discharge process.